The Effect Of Tem-Umw Ultraviolet Sterilization Box Radiation On Paper Money Bacteria : Paper Money Bacteria - Sutiari, Desak Ketut; Abidin, Muhammad; Somayasa, Wayan; Hamrin, La Ode (STIKes Mandala Waluya Kendari, 2024)
Background: TEM-UMW UVC sterilization cabinets have been designed using door safety systems and timers. Door security systems are designed to avoid exposure to UVC rays in users. Sterilization is carried out to improve the quality of public health and ensure the cleanliness of an object. Sterilization using exposure to UVC light can decide the survival of micrinorganisms or bacteria. This causes UVC light to be widely used as a sterilizer for non-living objects. This study was conducted to determine the effectiveness of UVC exposure time to bacterial colonies on banknotes. Exposure is done by making one sample as a cocontroller. Methods: This study banknotes are illuminated at intervals of 0, up to 30 minutes using a sterilization cabinet. The number of bacteria on the banknote is calculated by the bacterial culture method and then analyzed using a counter colony. Results: Based on the results of the analysis of known samples without exposure to light, the number of bacteria was about 250 colonies when the first minute of exposure bacteria was reduced to 38 colonies. The number of colonies on banknotes is constantly reduced if the length of exposure is increased. By the 30th minute the number of colonies becomes 6 Conclusions: The results shown Exposure using UVC through strilization cabinets can kill bacteria on banknotes. The optimal exposure time of UVC rays affecting the number of bacterial colonies on the Rp. 2000 banknote is 25 -30 minutes.